In vitro Antioxidant Potentiality of Purified Anthocyanin from Floral Petals of Wild Balsam Species (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Phenolics are the largest group of phytochemicals ubiquitous in plant species with considerable interest economically. Recently, search of novel polyphenols increasingly becomes an area of intensive pharmacological research due to their multiple bioactive features such as antioxidant, antimicrobial, anti-carcinogenic, anti-viral and anti-inflammatory potentialities. Anthocyanins are flavonoid group of polyphenols, a group predominant in flowers, fruits and vegetables. The flavonoids, perhaps the unique single group of phenolics in foods, comprise a group of over 4200 C15 aromatic molecules with multiple structural patterns. The functions of anthocyanins as medicinal have been well-accepted in folk medicine throughout the world. In fact, these molecules are connected to an amazingly broad-based range of health benefits. In this juncture, the aim of this work was to evaluate the antioxidant activities of purified anthocyanin from wild balsam species. Initially, anthocyanin was extracted from floral leaves of wild balsam species and purified by chromatographic techniques. Subsequently, it was subjected to NMR and LC MS analysis. The major fractions identified were hesperidin, dimethoxy antirrhinin and trimethoxy antirrhinin. Further, the anthocyanin extracts were subjected to in vitro protocols like 2,2’-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) radical cation, DPPH scavenging assay, ferric reducing antioxidant power (FRAP), beta carotene bleaching assay, metal chelating and H2O2 scavenging power. Interestingly, ABTS, FRAP analyzes yielded significant results as compared to others. The data were comparable with that of synthetic antioxidants like ascorbate and catechin. Meanwhile, beta carotene and H2O2 scavenging assay showed moderate results. DPPH and metal chelating protocols displayed the values 71% and 64% respectively at 25 µg/ml concentration. This study provides model systems for the evaluation of natural antioxidants like anthocyanin. Future in vivo clinical studies are warranted to confirm the obtained data.